1927 Haw. Sess. Laws 209-17, §§ 10-11, 17 - (:unkn) unknown (My University, 1927)
AN ACT Regulating the Sale, Transfer and Possession of Certain Firearms and Ammunitions, and Amending Sections 2136, 2137, 2138, 2139, 2140, 2141, 2142, 2143, 2146 and 2147 of the Revised Laws of Hawaii 1925 (the "Small Arms Act"), §§ 10-11, § 17: Requires all dealers to be licensed to expose to sale, transfer, have in possession with intent to sell, any pistol or revolver. Licenses shall be granted by the licensing authority, whose form is prescribed by the treasurer. Violators punished by fine of not more than one thousand dollars or imprisonment of not more than one year, or both.
Keywords: LICENSE - DEALERS